Optimization of industrial-scale composting of dewatered pig slurry and olive mill waste using discarded tennis balls as an inert bulking agent - Aviñó-Calero, Juan; Santateresa, Ernesto; Orden, Luciano; Marks, Evan A.N.; Martínez-Sabater, Encarnación; Andreu-Rodríguez, Francisco Javier; Sáez-Tovar, José; Pérez-Murcia, María Dolores; Bustamante, María Ángeles; Moral, Raúl (Elsevier, 2024)
Material shortages in composting may pose limits or logistical problems in certain regions, which can be addressed with inert and reusable wastes. Very little research has been conducted on the subject of using alternative synthetic wastes as structuring agents to improve composting process parameters. The present work aimed to evaluate the use of used tennis balls (TB) as an inert bulking agent. Composting was carried out in an industrial composting plant with a ternary mixture of olive mill waste, the solid fraction of dewatered pig slurry, urban pruning residues, with the addition of TB as a synthetic bulking agent. Composting process parameters, monitored throughout the composting cycle, showed that TB significantly affected the thermal composting process parameters, with increases in operating temperatures, exothermic index, and mineralization of organic matter. Also, compost properties were seen to be of equal or superior quality at the end of the composting with addition of TB. These are the first experimental results testing the effect of a spherical synthetic reutilized product such as TB on composting processes, which was additionally carried out at an industrial scale, showing that using discarded materials such as used tennis balls can improve the efficiency and economy of composting.